Montgomery's Auditing. - Causey, Denzil Y.; Dominiak, Gere (The Accounting Review, 1977)
Abstract Reviews the book "Montgomery's Auditing," by Philip L. Defliese, Kenneth P. Johnson and Roderick K. Macleod.